Association between maternal age at childbirth and metabolic syndrome in postmenopausal women: Korea National Health and Nutrition Examination Survey 2010 to 2012. Issue 2 (February 2017) - Shin, Jae Eun; Han, Kyung Do; Shin, Jong Chul; Lee, Young; Kim, Sa Jin
Abstract: Objective: The aim of this study was to evaluate the relationship between maternal age at childbirth and metabolic syndrome in postmenopausal women. Methods: We carried out a cross-sectional study on 3, 956 Korean postmenopausal women who participated in the Korea National Health and Nutrition Examination Survey from 2010 to 2012. Multivariate logistic regression was used to evaluate the association between maternal age at first and last childbirth and metabolic syndrome, with adjustment for potential confounding variables. Results: Women with metabolic syndrome had younger age at first delivery (23.3 ± 0.1 vs 24.4 ± 0.1 y, P  < 0.001) and an older age at last delivery (30.8 ± 0.1 vs 30.3 ± 0.1 y, P  = 0.011) than those without metabolic syndrome. After adjustments for confounding factors, earlier ages of first and last childbirth were positively associated with metabolic syndrome. The odds ratio (OR) was 2.157 (95% CI 1.256-3.705) for age at first childbirth, and 1.639 (95% CI 1.118-2.403) for age at last childbirth. Among the components of metabolic syndrome, only fasting glucose was positively associated with early age at first childbirth (OR 1.86; 95% CI 1.065-3.249) and early age at last childbirth (OR 1.71; 95% CI 1.197-2.444). Conclusions: A younger maternal age at first and last childbirth was independently associated with a higher risk of metabolic syndrome in postmenopausal women. Advanced maternal age at last childbirth was, however, not an independent risk factor for metabolic syndrome.